Estudo das propriedades eletroquímicas e magnéticas do polipirrol - Marchesi, Luís Fernando Quintino Pereira (Universidade Federal de São Carlos, 2010)
In this work the electrochemical degradation of polypyrrole films was studied by means of an applied overpotential and the magnetic properties of polypyrrole pellets, when these were modified by the incorporation of metallic species. The films studied in the electrochemical degradation were grown potentiostatically at 0.75 V vs. SCE, up to a charge of 80 mC in a HCl solution, using LiClO4 as support electrolyte. The degradation process took place by an applied potential of 0.58 V vs. SCE, accompanied by cyclic voltammetry and electrochemical impedance spectroscopy measurements. The voltammograms showed the decrease of the polypyrrole redox properties with the degradation process, and the impedance measurements, that were interpreted using transmission line models, showed that the degradation process affects the interfacial polypyrrole properties, once the polymeric resistivity and the time constant of the diffusional process in the pores remained constant. The magnetic measurements of the polypyrrole pellets showed that the sample ferromagnetism is dependent of the synthesis parameters, such as temperature and monomer/oxidant ratio. The magnetic properties of the polypyrrole pellets also shown to be dependent of the iron and cooper particles incorporated in the sample during the synthesis, which is interesting, once independently of the nature of the magnetic particle, the changes that occurred in the magnetic properties of the polypyrrole were similar.
Keywords: Físico-química; Polipirrol; Impedância eletroquímica; Eletroquímica; Magnetismo; CIENCIAS EXATAS E DA TERRA::QUIMICA